Solid Modeling and Applications Rapid Prototyping, CAD and CAE Theory - Um, Dugan (Springer International Publishing : Imprint: Springer, 2016)
The lessons in this fundamental text equip students with the theory of Computer Assisted Design (CAD), Computer Assisted Engineering (CAE), the essentials of Rapid Prototyping, as well as practical skills needed to apply this understanding in real world design and manufacturing settings. The book includes three main areas: CAD, CAE, and Rapid Prototyping, each enriched with numerous examples and exercises. In the CAD section, Professor Um outlines the basic concept of geometric modeling, Hermite and Bezier Spline curves theory, and 3-dimensional surface theories as well as rendering theory. The CAE section explores mesh generation theory, matrix notion for FEM, the stiffness method, and truss Equations. And in Rapid Prototyping, the author illustrates stereo lithographic theory and introduces popular modern RP technologies. Solid Modeling and Applications: Rapid Prototyping, CAD and CAE Theory is ideal for university students in various engineering disciplines as well as design engineers involved in product design, analysis, and validation.